PENINGKATAN HASIL BELAJAR DAN MOTIVASI PESERTA DIDIK DENGAN MODEL PEMBELAJARAN PBL BERBANTUAN KUIS INTERAKTIF PADA MATA PELAJARAN IPAS KELAS IV SD TAHUN 2024/2025 - Farida Amalia Shofiaty; Naufal Nafi'ardina; Oktaviarta Nafiatul Ariffah; Rusnilawati; Meilani Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objective of this classroom action research is to enhance both academic performance and learning motivation among fourth-grade students at SD Negeri Djama'atul Ichwan Surakarta in the IPAS subject through the implementation of the Problem-Based Learning (PBL) approach, supported by interactive quizzes. The low understanding and motivation of students in learning IPAS is the background of this research. The method of classroom action research (PTK) was applied to this study with two cycles in it, which was preceded by a pre-cycle stage. A total of 24 students in class IV D in the 2024/2025 academic year at SD Djama'atul Ichwan Surakarta became the research subjects. Data were collected through motivation questionnaires, learning assessments, and observation sheets. The data analysis combined quantitative methods with descriptive qualitative interpretation. The results showed a noticeable improvement in both learning outcomes and student motivation. During the pre-cycle phase, the percentage of students meeting the learning criteria was 58.3%. After applying the PBL model supported by interactive quizzes, the percentage increased to 79.16% in the first meeting of cycle I and 70.83% in the second meeting, further increasing to 75% in the first meeting of cycle II and reaching 83.3% in the second. Student motivation also improved, with scores rising from 71.92% in the first cycle to 77% in the second which was included in the high motivation to very high motivation category. These findings suggest that the use of the PBL model along with interactive quizzes is an effective strategy to enhance student learning outcomes and motivation in IPAS subjects.